2017
DOI: 10.18203/2394-6040.ijcmph20170759
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with therapeutic non-compliance among type 2 diabetes mellitus patients in Chidambaram, Tamilnadu, India

Abstract: Background: Diabetes mellitus is one of the most common non-communicable diseases causing many serious complications worldwide. Therapeutic non-compliance leads to treatment failure thus making diabetes a serious problem to both the individuals and the health care providers. There are many factors which influence patient’s compliance. The aim of this study is to assess the frequency of therapeutic compliance and factors associated with therapeutic non-compliance.Methods: A descriptive cross-sectional study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…FDCs help reduce the dose of individual drugs and thereby reduce dose-related side effects and pill burden, indirectly affecting treatment compliance. A significant association was found between noncompliance and frequent dosing and multiple drugs in a study done by Sharma T et al [20] However, there was no significant association found between poor compliance and the number of drugs in this study, and a similar result was also reported in a study done by Manobharathi et al [4] in Tamil Nadu.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…FDCs help reduce the dose of individual drugs and thereby reduce dose-related side effects and pill burden, indirectly affecting treatment compliance. A significant association was found between noncompliance and frequent dosing and multiple drugs in a study done by Sharma T et al [20] However, there was no significant association found between poor compliance and the number of drugs in this study, and a similar result was also reported in a study done by Manobharathi et al [4] in Tamil Nadu.…”
Section: Discussionsupporting
confidence: 83%
“…In a medical context, compliance refers to a patient both agreeing to and then undergoing some part of their treatment program as advised by their doctor/health care worker [3]. According to the World Health Organization (WHO), adherence to long-term therapy for chronic illnesses averages only around 50% in developed countries [4]. The WHO emphasized that “increasing the effectiveness of adherence interventions may have a greater impact than improvement in specific medical treatments [5].…”
Section: Introductionmentioning
confidence: 99%